(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
A cooperative communication system (CCS) aims to reduce the effect of multipath fading. There are two types of protocol relay techniques, namely, amplify and forward (AF) and decode and forward (DF). Hybrid relay selection (HRS) is a composite of AF and DF protocols where the relay will select one protocol using hybrid relay selection technique. If the information is accepted, then the relay node will pick to send information with the DF protocol or vice versa. Hybrid relay protocols on cooperative communication system using AF relay protocol, DF, and hybrid with Selection Combining (SC) technique. Hybrid Relay Selection System is used to reduce Bit Error Rate.